2015
DOI: 10.1007/s11357-015-9821-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the anorexia of aging—a review

Abstract: Many, even healthy, older people fail to adequately regulate food intake and experience loss of weight. Aging-associated changes in the regulation of appetite and the lack of hunger have been termed as the anorexia of aging. The etiology of the anorexia of aging is multi-factorial and includes a combination of physiological changes associated with aging (decline in smell and taste, reduced central and peripheral drive to eat, delayed gastric emptying), pathological conditions (depression, dementia, somatic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
164
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(178 citation statements)
references
References 130 publications
3
164
1
10
Order By: Relevance
“…The relative slowing of gastric emptying with ageing may have implications for appetite regulation, potentially contributing to the so-called 'anorexia of ageing' [10,18] -the reduction of appetite and energy intake evident in older when compared with young adults -which is likely to predispose older people to pathological weight loss, particularly affecting skeletal muscle. Even 'healthy' ageing is characterized by altered regulation of appetite and energy intake, which are both less in young adults, and which appear to be less sensitive to further suppression by ingestion of nutrients including protein ( Fig.…”
Section: Stomachmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative slowing of gastric emptying with ageing may have implications for appetite regulation, potentially contributing to the so-called 'anorexia of ageing' [10,18] -the reduction of appetite and energy intake evident in older when compared with young adults -which is likely to predispose older people to pathological weight loss, particularly affecting skeletal muscle. Even 'healthy' ageing is characterized by altered regulation of appetite and energy intake, which are both less in young adults, and which appear to be less sensitive to further suppression by ingestion of nutrients including protein ( Fig.…”
Section: Stomachmentioning
confidence: 99%
“…Malnutrition is a common condition in elderly residents in long-term care (85%), as well as in hospitalized (23-62%) and community dwelling elderly (15%) [10]. The growing awareness of the prevalence of undernutrition in older people and recognition of the adverse effects of major muscle loss during ageing has led to an increase in the use of oral highprotein supplements to increase the intake of protein and energy in the elderly population and, thereby, attenuate the loss of body weight and muscle mass [11].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults suffer from physiological changes in appetite (anorexia of aging), gastrointestinal physiology, and immune function all contributing to undernutrition [81]. In addition, undernutrition in older adults often coincides with (chronic) diseases like neoplasms, leading to cachexia.…”
Section: Microbial Characteristics In Undernutritionmentioning
confidence: 99%
“…Decreased meal consumption results in poor nutrition, dehydration, poor general condition, and decreased immune and cognitive function, and is a major factor affecting independent living. It has also been reported to contribute to aspiration pneumonia and mortality . Furthermore, reduced appetite in older people with dementia is an important issue for their families and nurses.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported to contribute to aspiration pneumonia and mortality. 3 Furthermore, reduced appetite in older people with dementia is an important issue for their families and nurses. Several studies have reported approaches to treat decreased appetite and meal consumption problems in persons with dementia.…”
Section: Introductionmentioning
confidence: 99%